MONITORING KELEMBABAN TANAH PERTANIAN MENGGUNAKAN SOIL MOISTURE SENSOR FC-28 DAN ARDUINO UNO - Husdi Husdi (ILKOM Jurnal Ilmiah, 2018)
Land as the main factor in agriculture must be considered as well as possible in order to provide the expected results. One of them is by using computer and internet technology to monitor soil moisture. Soil moisture is one of the environmental factors that affect plant growth. One of the innovations in information and communication technology in agriculture is the use of the Internet of Things. By using the Internet of Things, it can be done to monitor soil moisture that is used as a planting medium for horticultural crops. knowing the value of soil moisture will be very useful to be able to determine the steps or handling of the soil. The test results show that the measurement of soil moisture using a soil moisture sensor can work well and display information on the value of soil moisture. Based on the results and analysis, it can be concluded that the results of monitoring the soil moisture monitoring system can already be used to monitor agricultural land. So that the results of this study are expected to help farmers in making decisions based on information about the value of soil moisture that has been obtained. The final result obtained from the reading of the sensor value is wet, moist and dry according to the set value of the Analog Data. That is wet condition when getting output with lower limit range of 150 and upper limit of 339, humid condition when getting output with lower limit range 340 upper limit of 475, dry condition when getting sensor value with lower limit range is 476 and upper limit is 1023.